Chemical non-equilibrium flow analysis of H2 fueled scramjet nozzle. (March 2015) - Huang, Yue; Wang, Peiyong; Dou, Yang; Xing, Fei
Abstract: A numerical analysis of the chemical non-equilibrium phenomena in a scramjet nozzle has been performed using CHEMKIN software. Different operating conditions of the Hyshot scramjet nozzle were simulated and analyzed. Three chemical status, frozen flow, equilibrium flow, and non-equilibrium flow, were tested and compared to demonstrate the chemical reaction effect on nozzle flow field. The real non-equilibrium flow simulation result is between those of the two limiting cases: frozen flow and equilibrium flow, and is closer to that of frozen flow. With complete combustion condition at nozzle inlet, the radical recombination reaction releases tremendous amount of heat and this heat is mainly used to increases gas temperature and has only slight increasing effect on thrust. With incomplete combustion condition at nozzle inlet, both combustion reaction and radical recombination occur in the nozzle, the effect of reaction heat release on thrust depends on the degree of combustion completeness at nozzle inlet, it could increase thrust tremendously compared to frozen flow.